Societal trust and corporate bankruptcy - Jha, Anand; Oyotode-Adebile, Renee; Raja, Zubair Ali (Journal of Financial Stability, 2024)
We find that societal trust—the extent to which residents of a country trust others—is associated with a more efficient bankruptcy process. Bankruptcy resolutions are faster, efficient outcomes are more likely, and the value lost during the bankruptcy process is lower in countries with higher societal trust. This effect of societal trust on the efficiency of the bankruptcy process is more pronounced in countries with low-income per capita, and in corrupt countries. Our results are derived from the analysis of survey data concerning the outcomes of a hypothetical firm's bankruptcy in 99 countries from 2004 to 2020, a dataset also utilized by Djankov et al. (2008).